The possibility of producing an Eco-Friendly refractory concrete - Whab Abd; Mohammed Salman; Shatha Hasan (Engineering and Technology Journal)
The quantity of waste generated during construction and demolition keeps rising annually. Refractory bricks are wastes that have a detrimental effect on the environment. This paper investigates the reuse of refractory brick wastes to create environmentally friendly refractory concrete. To accomplish this goal, two percentages 10 and 25% of alumina cement will be substituted for bauxite powder, and alumina brick as the aggregate will be used instead of the natural aggregates. For each of the six types, a mix of refractory concrete (RFC), 14% water content, and a 1:3 cement/ aggregate ratio. The cast samples were stored at laboratory temperature for a full day while still in their molds. The cast samples were left for (24) hours at laboratory temperature in 100% relative humidity. After that, they were opened and placed in water for 7 days to cure. The specimens were placed in an oven to dry at 110 ℃ for 24 hours after seven days of curing in water. The samples were burned for two hours at temperatures between 1000–1100 ℃ at a rate of 3.33 ℃/min. After that, they were cooled to 25 ℃ before being tested. Then, the cast samples were tested to determine the bulk density, shrinkage, compressive strength, modulus of rupture, and weight change. The produced RFC performed almost comparably to those obtained on conventional RFC. This implies that waste alumina bricks as aggregate, with bauxite powder, can be used to manufacture RFC.